Pengaruh Literasi Pemasaran, Sertifikasi Halal Self Declare Terhadap Keberhasilan Usaha Mikro Kecil Menengah Melalui Entepreneur Knowledge - Romadhon, Gilang; Susyanti, Jeni; Saraswati, Ety (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The purpose of this study was to determine the effect of marketing literacy, self declare halal certification on the success of MSMEs through entrepreneur. The population of this study were culinary subsector MSMEs in Malang City with a sample of 80 respondents. This research uses quantitative methods with Smart Partial Least Square path analysis techniques, analyzed using the SmartPLS version 4.0 application. The results of this study indicate that: (1) marketing literacy has no effect on business success, (2) marketing literacy affects entrepreneur knowledge, (3) self declare halal certification affects business success, (4) self declare halal certification has no effect on entrepreneur knowledge, (5) entrepreneur knowledge has no effect on business success, (6) entrepreneur knowledge is not proven to mediate the effect of marketing literacy on business success, and (7) entrepreneur knowledge is not proven to mediate the effect of self declare halal certification on business success. Keywords: Marketing Literacy; Self Declare Halal Certification; Entepreneur Knowledge; Business Success; MSMEs